Erythema Gyratum Repens: A Rare Paraneoplastic Rash - Michael E Winters; Marina Gore (Western Journal of Emergency Medicine, 2011)
Erythema gyratum repens (EGR) is a rare, and characteristic, paraneoplastic rash associated with a variety of malignancies, most notably lung, esophageal, and breast cancers. This case report details the appearance, epidemiology, diagnosis, and treatment of EGR. Prompt identification of EGR is essential, as the rash often precedes the diagnosis of malignancy by several months. Urgent patient referral to evaluate for malignancy is crucial, as this may lead to decreased morbidity and mortality. [West J Emerg Med. 2011;12(4):556–558.]